EXPANDED FAQS ON ADVANCE CARE PLANNING: DRIVEN BY THE COMMUNITY. Issue 2 (1st June 2013) - Kelly, C; Maloney, M A; Smith, L; Puls, K; Spillane, V; Sutton, E; Silvester, W
Abstract : Background: In March 2011, Respecting Patient Choices at Austin Health established a Volunteers Program to provide education to community groups about Advance Care Planning (ACP). Commencing with 18 Frequently Asked Questions (FAQs), this expanded to 92. Aim: To review the need for, the benefits and implications of expanded FAQs. Methods: The FAQs at programme commencement were compared with the FAQs by December 2012. Volunteers were interviewed regarding the FAQ development. Results: The expansion of the FAQs was driven by consumer demand at Information Sessions; 18 broad questions were not satisfactory. The 92 questions (not all asked at each session) could be grouped into themes. Themes included: Role of the GP; Conflict; Competency; Legal Issues; Organ Donation; ACP in Critical situations; Euthanasia; Dying with Dignity, Religion and ACP. The attendee feedback regarding the sessions and questions was very positive; 94.2% of 309 attendees agreed/strongly agreed that their questions were answered; 96.8% agreed/strongly agreed that the presentation increased their ACP knowledge. Discussion: The FAQs were expanded to meet community expectations about information provided at the sessions. The benefit of expanding this list was that new Volunteers would be aware of the type of questions that would be asked, and that consistent answers could be provided. The implication is that Volunteers providing information to community groups need to have detailed knowledge of the entire ACP process. Conclusion: Expanded FAQs required very specific responses, provided greater satisfaction and meant that Volunteers needed high level knowledge of the ACP process.